Pengaruh Pemahaman Peraturan Pajak, Tarif Pajak, Lingkungan dan Kesadaran Wajib Pajak Terhadap Kepatuhan Wajib Pajak - Yunus Nurhasan; Rijal Arslan; Chaeru Syahru Ramdhani; Rananda Septanta (AKADEMIK: Jurnal Mahasiswa Humanis, 2026)
The rapid growth of online shopping in Indonesia has created significant potential for tax revenue, prompting the government to strengthen the regulation of taxation in E-Commerce transactions. However, efforts to optimize state revenue face several challenges, including taxpayers’ limited understanding of tax regulations, perceptions of tax rates, environmental influences, and varying levels of taxpayer awareness. This study aims to analyze the effect of these factors on taxpayer compliance among individual taxpayers engaged in online shopping activities. This quantitative research employed a survey method and was conducted at the Primary Tax Office (KPP Pratama) Tangerang. A total of 200 individual taxpayers were selected using simple random sampling. Data were collected through the distribution of Likert-scale closed-ended questionnaires and processed using SPSS 25. Multiple linear regression analysis was performed to examine both simultaneous and partial influences of the variables. The findings indicate that Understanding of Tax Regulations, Tax Rates, Environment, and Taxpayer Awareness simultaneously affect Taxpayer Compliance. However, partial testing reveals that only Understanding of Tax Regulations and Taxpayer Awareness have a significant positive effect on Taxpayer Compliance. These results highlight the importance of improving taxpayer knowledge and awareness to enhance compliance in the growing E-Commerce sector.